Uji Aktivitas Antibakteri Kombinasi Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) dan Daun Kelor (Moringa oleifera Lam.) terhadap Bakteri Penyebab Jerawat Propionibacterium acnes: Penelitian - Agustina, Mela; Anggista Putri, Nopi; Safutri, Wina; Mayola Pisacha, Iga (PT Kalbe Farma Tbk., 2025)
Introduction: Acne is a skin disease that is often found in many teenagers to young adults. Propionibacterium acnes is one of the causes of acne infection with a prevalence of 12.9%. As long-term inappropriate use of antibiotics can cause resistance, traditional medicine using natural ingredients can act as an alternative. The secondary metabolite compounds from binahong (Anredera cordifolia (Ten.) Steenis) leaves and moringa (Moringa oleifera Lam.) leaves are believed to have antibacterial activity. This study aims to determine the antibacterial activity of a combination of binahong leaves and moringa leaves in inhibiting the growth of acne-causing bacteria, Propionibacterium acnes. Methods: This quantitative experimental research study tested the antibacterial properties of binahong leaves and moringa leaves againstPropionibacterium acne with random design (RAL) of 11 treatments with 3 repetitions. Bacterial test used paper disc diffusion with a single concentration of 20%, 40%, 60% and a combination of 20%:20%, 40%:60%, and 60%:40%, with clindamycin as positive control and sterile aquadest as negative control. Results: The phytochemical screening results were that binahong leaves and moringa leaves contained alkaloids, tannins, saponins, and flavonoids while the results of the antibacterial activity test were that the 60%:40% combination was more effective in inhibiting the growth of Propionibacterium acnes with an inhibition zone diameter of 26.7 mm ± 2.0 (strong). Conclusion: Binahong leaves and Moringa leaves contain secondary metabolite compounds of tannins, alkaloids, saponins, and flavonoids, and have antibacterial activity. Binahong leaves and moringa leaves can inhibit the growth of bacterium Propionibacterium acnes with a strong inhibition zone category.